Proceedings of the Ocean Drilling Program, 160 Scientific Results 1998
DOI: 10.2973/odp.proc.sr.160.004.1998
|View full text |Cite
|
Sign up to set email alerts
|

The formation of Pliocene Mediterranean sapropels: constraints from high-resolution major and minor element studies

Abstract: Two Pliocene Mediterranean sediment cores from Sites 964 (Pisano Plateau, Ionian Basin) and 967 (lower northern slope of Eratosthenes Seamount, south of Cyprus), which comprise a total of 428 samples, have been analyzed for major and minor elements (Si, Ti, Al, Fe, Mg, Ca, K, Ba, Cr, Ni, V, Zn, and Zr) by X-ray fluorescence analysis at a depth resolution of 3-4 cm. Core 160-964C-9H comprises five sapropels with up to 9.7% total organic carbon (TOC), one 2.5-m-thick turbidite, and a 50-cm segment of a second tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…North African dust can be traced by identifying hematite and goethite, which provide information concerning the abundance of transported dust [ Larrasoaña et al , 2003a]. Geochemical data in the eastern Mediterranean region can enable discrimination between materials originating from the Aegean or North Africa [ Bergametti et al , 1989; Wehausen and Brumsack , 1998; 2000; Lourens et al , 2001].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…North African dust can be traced by identifying hematite and goethite, which provide information concerning the abundance of transported dust [ Larrasoaña et al , 2003a]. Geochemical data in the eastern Mediterranean region can enable discrimination between materials originating from the Aegean or North Africa [ Bergametti et al , 1989; Wehausen and Brumsack , 1998; 2000; Lourens et al , 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations demonstrated that Al and Ca, and the ratios Ni/Al, Si/Al, Fe/Al, and Ti/Al are indicative of different sediment origins and can be linked to environmental conditions in certain source areas [e.g., Bergametti et al , 1989; Wehausen and Brumsack , 1998; Lourens et al , 2001]. Ni is associated with ultramafic rocks, which in this area are exclusively found in the Aegean region, whereas Si/Al and Ti/Al represent the African sources [ Wehausen and Brumsack , 2000].…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by several investigations (Wehausen and Brumsack, 1998;Emeis et al, 2000;Revel et al, 2010;Blanchet et al, 2014). However, it is in conflict with some other studies (Adamson et al, 1980;Krom et al, 1999aKrom et al, , 2002Box et al, 2011) that have argued for a lower Blue Nile sediment discharge during the warm and humid Holocene AHP and higher fluxes during dry climate phases.…”
Section: Feedback Effectsmentioning
confidence: 53%
“…The sediments recovered from ODP 967A were composed of bioturbated nannofossil oozes, nannofossil clays and sapropels, which could be constrained within an astronomical chronology Sakamoto et al, 1998;Kroon et al, 1998) based on the timescale of Lourens et al (1996). Previous investigations of ODP 967A have provided geochemical (Wehausen and Brumsack, 1998;Lourens et al, 2001) and rock magnetic (Larrasoana et al, 2003) evidence for aeolian dust input, originating from Northern Africa.…”
Section: A Mediterranean Test Case: Odp Site 967mentioning
confidence: 99%